Rational pharmacotherapy of chronic heart failure with increased endothelin-1 activity: beta-adrenoblocker nebivolol place - L. I. Olbinskaya; Yu. I. Naymann (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To optimize chronic heart failure (CHF) pharmacotherapy, basing on endothelin (ET) system activity, functional and cardio-hemodynamic parameters, and their dynamics in beta-adrenoblocker nebivolol therapy. Material and methods. The study included 52 patients with coronary heart disease and systolic CHF, Functional Class (FC) II-IV by NYHA. Pulmonary hypertension (PH) was registered in 27 participants. The control group included 10 age-matched healthy individuals. CHF patients were divided into two groups: Group 1 (n=28) additionally received nebivolol (5 mg/d); Group 2 (n=24) continued standard treatment. At baseline and 10 week slater, 6-minute walk test (6MWT), quality of life (QoL) questionnaire survey, and echocardiography were performed. In 40 patients, plasma ET-1 level dynamics was assessed. Results. Ten weeks later, in nebivolol group, CHF FC decreased, 5MWT distance increased (р=0,0046) as well as left ventricular ejection fraction, QoL significantly improved. No significant changes were observed in Group 2. Maximal ET-1 level was registered in FC IV CHF or PH patients. ET-1 concentration significantly correlated with mean and systolic pulmonary artery pressure (PAP), right ventricular myocardial diameter and wall thickness. After 10 weeks of nebivolol therapy, ET-1 level significantly decreased in CHF and PH participants (р=0,0096). ET-1 concentration dynamics in nebivolol group correlated with PAP dynamics and increased physical stress tolerance (PST). Conclusion. ET-1 concentration increased in parallel with CHF FC and PAP increase. Nebivolol significantly improved myocardial contractility, prevented further myocardial remodeling, improved pulmonary hemodynamics, therefore enhancing PST and QoL. In PH patients nebivolol significantly decreased plasma ET-1 levels.